THE PHYSICAL TESTS FOR 13-15 YEAR OLD TABLE TENNIS PLAYERS - Liskustyawati, Hanik; Sulaiman, Sulaiman; Rachman, Hari Amirullah (The Journal of Educational Development, 2016)
The achievement of high performance and optimal physical quality is the requirement that can not be ignored by a coach because every sport requires physical quality levels that vary according to the required physical qualities of the sport. Today, there are many types of tests to determine physical capabilities that are used for identifying the talent of table tennis players of all age groups. The available physical tests have not been tested empirically against the physical performance of a table tennis player. This study aimed to develop appropriate physical tests for men and women’s table tennis players aged 13-15 years. The method used was research and development. The development steps included 1) a preliminary study, 2) needs analysis, 3) expert validation, 4) empirical validation, 5) evaluating the effectiveness. The research samples consisted of 73 men’s players and 68 women’s players aged 13-15 who were enrolled in the Indonesia table tennis club (PTMSI) in Central Java; the age chronologically following the practice for at least 2 years and the frequency of exercise being 3 times a week. The data were analyzed using inter-correlation and research instruments consisting of observations with the Likert scale in the form of a rating scale. The results of the research and development show that the appropriate physical tests for men and women’s players aged 13-15 years consist of 6 test items including arm span, hands reaction speed, a tennis ball catching-throwing test, shuttle run, 20-meter sprint and multistage running. The conclusions of this research are: the developed physical tests are appropriate for men and women’s table tennis players aged 13-15 years, including the length of arm span, speed of reaction hand, tennis ball catching-throwing test, shuttle run, 20-meter sprint, and multistage run tests.